Prevalence of group A streptococcal disease in North and Sub-Saharan Africa: a systematic review protocol. Issue 8 (27th August 2015) - Barth, Dylan D; Mayosi, Bongani M; Jabar, Ardil; Engel, Mark E
Abstract : Introduction: The true burden of group A streptococcal (GAS) disease in Africa is not known. GAS is a significant cause of mortality and morbidity on the global scale and in developing countries. According to Carapetis et al, the prevalence of severe GAS disease is at least 18.1 million cases with an incidence of at least 1.78 million cases per year. Methods and analyses: We aim to provide a systematic review of studies measuring the prevalence of GAS infection among people in North and Sub-Saharan African countries. A comprehensive literature search of a number of databases will be undertaken, using an African search filter, to identify GAS prevalence studies that have been published. Full copies of articles will be identified by a defined search strategy and will be considered for inclusion against predefined criteria. Statistical analysis will include two steps: (1) identification of data sources and documenting of estimates, and (2) the application of the random-effects and fixed-effects meta-analysis model to aggregate prevalence estimates, and to account for between study variability in calculating the overall pooled estimates and 95% CI for GAS prevalence. Heterogeneity will be evaluated using the I 2 statistic to determine the extent of variation in effect estimates that is due to heterogeneity rather than chance. This systematic review protocol was prepared according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses Protocols (PRISMA-P) 2015 Statement. This review will provide updated evidence of a review published in 2009. Our data will have implications for the development of a GAS vaccine. Ethics and dissemination: Ethics approval is not required for this study given that this is a protocol for a systematic review of published studies. The results of this study will be disseminated through a peer-reviewed publication and conference presentation. Systematic review registration number: PROSPERO CRD4201401290 0. (http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42014012900 ).